Decreased Sclerostin Secretion in Humans and Mice With Nonalcoholic Fatty Liver Disease - Zhou, Fangli; Wang, Yan; Li, Yujue; Tang, Mengjia; Wan, Shan; Tian, Haoming; Chen, Xiang (Frontiers in Endocrinology, 2021)
Objectives: Growing evidence argues for a relationship between liver and bone metabolisms. Sclerostin is a secreted glycoprotein and could antagonize osteoblast-mediated bone formation. Previous studies indicated that circulating sclerostin levels may be associated with metabolic parameters with inconsistent results. This study was designed to evaluate serum sclerostin in patients with or without nonalcoholic fatty liver disease (NAFLD) and to analyze its relationship with metabolic parameters in different populations. Methods: A cross-sectional study was designed and 168 NAFLD subjects and 85 control subjects were included in this study. Mouse models of NAFLD were also induced by high-fat diet and mRNA expression levels of sclerostin in bone and liver tissues were measured. Results: Our study suggested that circulating sclerostin levels were significantly lower in NAFLD subjects compared with normal controls. In NAFLD subjects, sclerostin was negatively correlated with multiple metabolic parameters, including waist circumference, urea, hepatic enzyme, gamma-glutamyl transpeptidase, and triglyceride, while such correlation was not significant in control subjects. Circulating sclerostin was also negatively correlated with fatty liver index in NAFLD subjects but not in control subjects. Mice fed on high-fat diet showed more lipid accumulation in the liver and bone marrow and lower sclerostin expression levels in both the bone and liver tissues. Conclusions: Our study suggested that the liver-lipid-bone interactions may play a key role in the abnormal bone metabolism in NAFLD, and circulating sclerostin may be a surrogate marker to reflect bone metabolism status in NAFLD subjects.